Effectiveness of Structured Training on Knowledge and Attitude Toward Research Among Medical Laboratory Technology Interns - Sharon Raju; Shivashankara AR; Claudia Johnny; Omkareshwar Patil; Praseena K; Nisha J Marla (RGUHS Journal of Allied Health Sciences)
Background Involving health science students in research fosters critical thinking and enhances their understanding of common clinical challenges. Structured research training and active participation in projects significantly improves the quality of care they deliver as future health professionals.Objectives The present study aimed to assess the knowledge and attitude of research among medical laboratory technology interns and to evaluate the effectiveness of a structured research training programme.Methods Twenty-six BSc Medical Laboratory Technology MLT interns from a health sciences college were evaluated for research knowledge and attitudes using validated questionnaires. Over their one-year internship they received 20 hours of research methodology training and conducted individual research projects. Pre- and post-internship assessments of knowledge and attitudes were conducted and compared to evaluate the impact of training.Results The MLT interns demonstrated a significant improvement in knowledge with post-training knowledge scores showing a marked improvement P lt0.001. A higher number of interns achieved very good and excellent grades after the training compared to pre-training scores. While interns initially displayed a favourable attitude toward research this attitude further improved following the program. Most interns disagreed that research was a waste of time or an added curricular burden. Participants recommended integrating research into the MLT curriculum.Conclusion Structured research training with interactive sessions and hands-on projects effectively enhanced knowledge and fostered a positive attitude toward research among medical laboratory technology interns. Integrating research into Allied Health Sciences curricula is recommended with a focus on innovative and interactive teaching methods to engage students in research.